PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Survey pada pelanggan KFC Store Merdeka Bandung) - Mirza Abdi Khairusy; Reni Febriani (Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the influence of quality product, quality service and customers satifaction PT Fast Food Indonesia Tbk KFC Store Merdeka Bandung. Using the explanatory survey, data were collected through questionnaires distributed to 89 respondents. Data were analyzed using descriptive statistical analysis and SPSS (Statistical Package for Social Sciences) Software IBM Version 23. From the data obtained, the result (1) quality product has a significant positive effect on customers satisfaction (2) Service quality has a significant positive effect on customers satisfaction (3) The quality product and service quality significant positive effect on customers satisfaction